(untitled) (Altre Modernità, 2023)
During the epidemic peaks of the early modern age, there were sharp increases in the production of printed materials, often on flysheets that today survive as unica: decrees of health offices, pre-printed passes, recipes for the body and soul, short chronicles and a large number of verse compositions. After a brief introduction to the medical-scientific context, the essay focuses on the publication of poetic texts and official documents. The former expressed the widespread mood of people exacerbated by the epidemic and discouraged by a science that did not provide effective therapeutic answers. The latter, the decrees of the Health Office, some drawn up in collaboration with physicians practising in the area, were decisive in containing the contagion, codifying health monitoring and techniques for disinfecting movable and immovable property. The substances used for disinfection were endowed with antibacterial properties that were also confirmed by the most recent biochemical studies: they were the most effective response to the disease, in stark contrast to the sterile landscape of academic discussions.